Pentaminomycins C–E: Cyclic Pentapeptides as Autophagy Inducers from a Mealworm Beetle Gut Bacterium - Sunghoon Hwang; Ly Thi Huong Luu Le; Shin-Il Jo; Jongheon Shin; Min Jae Lee; Dong-Chan Oh (Microorganisms, 2020)
Pentaminomycins C–E (1–3) were isolated from the culture of the Streptomyces sp. GG23 strain from the guts of the mealworm beetle, Tenebrio molitor. The structures of the pentaminomycins were determined to be cyclic pentapeptides containing a modified amino acid, N5-hydroxyarginine, based on 1D and 2D NMR and mass spectroscopic analyses. The absolute configurations of the amino acid residues were assigned using Marfey’s method and bioinformatics analysis of their nonribosomal peptide biosynthetic gene cluster (BGC). Detailed analysis of the BGC enabled us to propose that the structural variations in 1–3 originate from the low specificity of the adenylation domain in the nonribosomal peptide synthetase (NRPS) module 1, and indicate that macrocyclization can be catalyzed noncanonically by penicillin binding protein (PBP)-type TE. Furthermore, pentaminomycins C and D (1 and 2) showed significant autophagy-inducing activities and were cytoprotective against oxidative stress in vitro.